Meson spectrum of Sp(4) lattice gauge theory with two fundamental Dirac fermions - Ed Bennett (Proceedings of 37th International Symposium on Lattice Field Theory — PoS(LATTICE2019), 2020)
We calculate the meson spectrum of the Sp(4) lattice gauge theory coupled to two fundamental flavours of dynamical Dirac fermions. We focus on some of the lightest (flavoured) spin-0 and spin-1 states. This theory provides an ultraviolet completion for composite Higgs models based upon the SU(4)/Sp(4) coset. We analyse the strongly coupled dynamics in isolation, without explicit coupling to the standard model. We carry out continuum extrapolations using dynamical ensembles generated at five different values of bare lattice coupling, and for several values of the bare fermion mass. We fit the resulting meson masses and decay constants to a low-energy effective field theory built along the ideas of hidden local symmetry. We also compare our results to those of other closely related lattice gauge theories, which have matter content consisting of two fundamental Dirac flavours.